KAJIAN ISLAM INTER DAN MULTI-DISIPLINER PEMIKIRAN FAZLUR RAHMAN TERHADAP PENDIDIKAN ISLAM - Elfiana; Mahmudi, Rosyid; Yani, Fitri; Iska, Syukri (STAI Nurul Falah Airmolek, 2024)
Fazlur Rahman is a Muslim scholar who has critical thinking about changes and developments in Islamic education. His thoughts were the pros and cons of his time and became an important study in this era. For this reason, research was carried out using the library research method. According to Rahman, the aim of Islamic education is to develop humans into fully functioning beings, and to save humans from themselves, for themselves, and to respect themselves. The current generation is facing serious problems due to dichotomization, which has led to the emergence of split personalities. To overcome this problem, the Islamic generation needs to receive modern education that integrates Islamic principles. Islamic education must be an agent of reform that can adapt to current developments without losing its fundamental values.